Erratum: Huizeling, E.; et al. Age-Related Changes in Attentional Refocusing during Simulated Driving. Brain Sci. 2020, 10, 530 - Eleanor Huizeling; Hongfang Wang; Carol Holland; Klaus Kessler (Brain Sciences, 2021)
The authors would like to submit the following corrections to the published paper [...]